2015
DOI: 10.2105/ajph.2014.302398
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits for Nontraumatic Dental Problems: A Mixed-Methods Study

Abstract: Emergency department dental visits are a significant and costly public health problem for vulnerable individuals. Future efforts should focus on implementing multilevel interventions to reduce ED dental visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
105
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 23 publications
15
105
0
2
Order By: Relevance
“…These findings were consistent with those of several studies that demonstrated that adolescents have a higher prevalence of use of services essentially characterized as an emergency for a dental problem when compared with children [14,15]. Emergency care of adolescents at UPAs can be considered a unique opportunity for their connection with the health system as there is a decrease in the search for health services during adolescence [16] and as the presence of toothache is associated with a higher demand for dental care [17].…”
Section: Discussionsupporting
confidence: 90%
“…These findings were consistent with those of several studies that demonstrated that adolescents have a higher prevalence of use of services essentially characterized as an emergency for a dental problem when compared with children [14,15]. Emergency care of adolescents at UPAs can be considered a unique opportunity for their connection with the health system as there is a decrease in the search for health services during adolescence [16] and as the presence of toothache is associated with a higher demand for dental care [17].…”
Section: Discussionsupporting
confidence: 90%
“…Claims data can potentially fill these cancer data gaps, and, as noted above, the linked SEER‐Medicare database has demonstrated the power of linkage of registry data with claims to obtain rich research data for individuals diagnosed with cancer at age 65 and older . APCD claims are being accessed for health research in Utah and in other states including Oregon, Colorado, and Massachusetts, but to our knowledge this is the first report demonstrating feasibility of linking APCD to a central cancer registry. Demonstrating a high linkage rate of patients is a first step toward using APCD to obtaining additional treatment, comorbidity, and outcome data for cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…The inappropriate use of emergency services for dental‐related problems extends beyond the UK . MED internationally are seeing high volumes of attendances for non‐traumatic dental problems, often caused by dental caries and are frequently managed in the emergency setting with pain relief or antibiotics .…”
Section: Introductionmentioning
confidence: 99%